An equiangular triangle adds up to 180 so divide that by 3, which is the number of sides, and you get, 60, therefore, each side is 60<span>° angle.</span>
Given:
A(-5,4)
B(3,4)
C(3,-5)
So point D is:
so point D is (-5,-5)
For AB is
Distance between two point is:
![\begin{gathered} (x_1,y_1)and(x_2,y_2) \\ D=\sqrt[]{(x_2-x_1)^2+(y_2-y_1)^2} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28x_1%2Cy_1%29and%28x_2%2Cy_2%29%20%5C%5C%20D%3D%5Csqrt%5B%5D%7B%28x_2-x_1%29%5E2%2B%28y_2-y_1%29%5E2%7D%20%5Cend%7Bgathered%7D)
so distance between A(-5,4) and B(3,4) is:
![\begin{gathered} D=\sqrt[]{(3-(-5))^2+(4-4)^2} \\ =\sqrt[]{(8)^2+0^2} \\ =8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20D%3D%5Csqrt%5B%5D%7B%283-%28-5%29%29%5E2%2B%284-4%29%5E2%7D%20%5C%5C%20%3D%5Csqrt%5B%5D%7B%288%29%5E2%2B0%5E2%7D%20%5C%5C%20%3D8%20%5Cend%7Bgathered%7D)
So AB is 8 unit apart.
For B(3,4) and C(3,-5).
![\begin{gathered} D=\sqrt[]{(3-3)^2+(-5-4)^2} \\ =\sqrt[]{0^2+(-9)^2} \\ =9 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20D%3D%5Csqrt%5B%5D%7B%283-3%29%5E2%2B%28-5-4%29%5E2%7D%20%5C%5C%20%3D%5Csqrt%5B%5D%7B0%5E2%2B%28-9%29%5E2%7D%20%5C%5C%20%3D9%20%5Cend%7Bgathered%7D)
So BC is 9 unit apart.
For fourth bush point is (-5,-5) it left of point C(3,-5) is:
![\begin{gathered} D=\sqrt[]{(3-(-5))^2+(-5-(-5))^2} \\ =\sqrt[]{(8)^2+0^2} \\ =8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20D%3D%5Csqrt%5B%5D%7B%283-%28-5%29%29%5E2%2B%28-5-%28-5%29%29%5E2%7D%20%5C%5C%20%3D%5Csqrt%5B%5D%7B%288%29%5E2%2B0%5E2%7D%20%5C%5C%20%3D8%20%5Cend%7Bgathered%7D)
so fourth bush is 8 unit left of C.
For fourth bush(-5,-5) below to point A(-5,4)
![\begin{gathered} D=\sqrt[]{(-5-(-5))^2+(4-(-5))^2} \\ =\sqrt[]{0^2+9^2} \\ =9 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20D%3D%5Csqrt%5B%5D%7B%28-5-%28-5%29%29%5E2%2B%284-%28-5%29%29%5E2%7D%20%5C%5C%20%3D%5Csqrt%5B%5D%7B0%5E2%2B9%5E2%7D%20%5C%5C%20%3D9%20%5Cend%7Bgathered%7D)
so fourth bush 9 units below of A.
The total distance phoebe has to drive each day (round trip) while her usual route is closed is 42 miles
<h3>What is a Pythagoras theorem?</h3>
The square of the longest side is equal to the square of the sum of the othersides.
Before we can calculate the total distance, we will need to get the hypotenuse on both sides using the Pythagoras theorem as shown:
H^2= 12^2 + 9^2
H² = 144 + 81
H² = 225
H = 15
For the other hypotenuse
h² = 12² + 5²
h² = 144 + 25
h² = 169
h = 13 mils
The total distance = 5 + 15 + 9 + 13
The total distance = 42 miles
The total distance phoebe has to drive each day (round trip) while her usual route is closed is 42 miles
Learn more on Pythagoras theorem here: brainly.com/question/12306722
Answer:
P(t) = 12e^1.3863k
Step-by-step explanation:
The general exponential equation is represented as;
P(t) = P0e^kt
P(t) is the population of the mice after t years
k is the constant
P0 is the initial population of the mice
t is the time in months
If after one month there are 48 population, then;
P(1) = P0e^k(1)
48 = P0e^k ...... 1
Also if after 2 months there are "192" mice, then;
192 = P0e^2k.... 2
Divide equation 2 by 1;
192/48 = P0e^2k/P0e^k
4 = e^2k-k
4 = e^k
Apply ln to both sides
ln4 = lne^k
k = ln4
k = 1.3863
Substitute e^k into equation 1 to get P0
From 1, 48 = P0e^k
48 = 4P0
P0 = 48/4
P0 = 12
Get the required equation by substituting k = 1.3863 and P0 = 12 into equation 1, we have;
P(t) = 12e^1.3863k
This gives the equation representing the scenario